Solve for y y-2=3(y-2)

Math
y-2=3(y-2)
Simplify 3(y-2).
Tap for more steps…
Apply the distributive property.
y-2=3y+3⋅-2
Multiply 3 by -2.
y-2=3y-6
y-2=3y-6
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 3y from both sides of the equation.
y-2-3y=-6
Subtract 3y from y.
-2y-2=-6
-2y-2=-6
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 2 to both sides of the equation.
-2y=-6+2
Add -6 and 2.
-2y=-4
-2y=-4
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=-4 by -2.
-2y-2=-4-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=-4-2
Divide y by 1.
y=-4-2
y=-4-2
Divide -4 by -2.
y=2
y=2
Solve for y y-2=3(y-2)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top